Transition-Metal-Free [3+2] Dehydration Cycloaddition of Donor-Acceptor Cyclopropanes With 2-Naphthols - Zhao, Hua; Shen, Peng; Sun, Dongru; Zhai, Hongbin; Zhao, Yufen (Frontiers in Chemistry, 2021)
A Brønsted acid-catalyzed of domino ring-opening cyclization transformation of donor-acceptor (D-A) cyclopropanes and 2-naphthols has been developed. This formal [3+2] cyclization reaction provided a novel and efficient access to the naphthalene-fused cyclopentanes in the absence of any transition-metal catalyst or additive. This robust procedure underwent smoothly on gram-scale to afford the corresponding product with comparable efficiency. Furthermore, the synthetic application of the prepared product has been demonstrated by its transformation into a variety of synthetically useful molecules.